Why the Center Can't Hold: A Diagnosis of Puritanized America - O'Neill, Tom (punctum books, 2016)
"Things fall apart; the centre cannot hold." These words from Yeats's poem "The Second Coming" provide Why the Center Can't Hold with its organizing theme. And although Yeats was describing the grim atmosphere of post-World War I Europe, O'Neill regards the poem's pronouncements as eerily predictive of the state of the world as we are currently observing it. O'Neill takes them as predictive of the agency in particular of the United States-the "Center"-in bringing about in the world the more general chaos we are now observing (relative to various refugee and migrant crises, the emergence of sophisticated and even postmodern forms of militant and cyber terrorism, banking and other monetary crises, environmental catastrophes under the aegis of climate change, the defunding of public higher education, the persistence of virulent forms of racism and other types of intolerance, the concentration of wealth in fewer and fewer hands, the marginalisation and even outright elimination of human labor forces, etc.). O'Neill provides historical analyses that illuminate why this is the case, and he also asks what changes in the United States - in its politics, in its socio-cultural formations, and in its beliefs and (supposedly common) values - might help us to avoid the inevitable (and lamentable) destruction that seems ahead